A Survey on IBM Watson and Its Services. Issue 1 (1st May 2022) - Kumar, Avinash; Tejaswini, Pallapothala; Nayak, Omprakash; Kujur, Anurag Deep; Gupta, Rajkiran; Rajanand, Ashish; Sahu, Mridu
Abstract: Artificial Intelligence (AI) is changing the modern way of lifestyle by helping the person do their jobs in an efficient manner. The AI is currently in its starting phase and from now on it is of great use. IBM Watson is an AI which is used globally by different organizations, institutes and corporations. In this paper we have created a chatbot using IBM Watson Assistance which is helpful in querying about the disease and hospitals related query. This paper also discusses IBM Watson in detail, its applications, its working and case studies on the use of IBM Watson in the field of healthcare, visual recognition and a software company named BOX.